Biodiversity and biogeography of zooxanthellate corals in Australasia revisited based on new data from the Kimberley - Richards, Zoe; Pichon, Michel; Wallace, Carden (Western Australian Museum, 2024)
The Kimberley Marine Region is a vast stretch of complex eastern Indian Ocean seascape spanning approximately six degrees of latitude and eight degrees of longitude. The region includes various habitats, including offshore reef and shoal systems, and a complex array of nearshore platform and fringing reefs along an estimated 12,000 km of the northern Western Australian coastline. Isolated from urban centres, the Kimberley features one of the world’s least anthropogenically impacted tropical reef ecosystems and is predicted to be a signifcant repository for coral biodiversity. However, little information has been publicly available to verify this. Here we report a revision of the zooxanthellate coral biodiversity of the Kimberley region based on new specimen records. Replicate belt transects were surveyed at 135 intertidal and subtidal stations spanning the inshore, mid-shelf and offshore Kimberley from 2009–2014. Nineteen thousand and eighty-six colonies and 333 species were counted and identifed on the belt transects, and an additional 62 species were recorded incidentally off transects. Combining the new museum-accessioned specimen records with recent specimen donations and published historical records from 1893 onwards resulted in an updated regional diversity estimate of 438 species of zooxanthellate reef-building corals in the Kimberley. This dataset extends the known distribution range of 85 species, 37 of which represent new records for Australia. Our results show that the Kimberley coral communities are heterogenous, with pronounced cross-shelf, depth, and subregional diversity patterns. Ashmore Reef, Cassini Island and Montgomery Reef are regional coral biodiversity hotspots. Goniastrea retiformis, Porites lutea, Dipsastraea pallida, Goniastrea favulus and Coelastrea aspera dominate the intertidal reef zones, whilst Porites lichen, Heliopora coerulea, Seriatopora hystrix, Goniastrea pectinata and Montipora aequituberculata dominate the subtidal reefs. This dataset suggests that the origins, biogeography, and connectivity within the Australasian region and the diversity of corals in the eastern Indian Ocean have been misinterpreted in the past. Overall, this study provides a revision of biodiversity and biogeographic patterns in Australia and highlights the importance of the Kimberley region as a nationally signifcant reservoir of tropical coral biodiversity with vital, yet under-studied, connections to the Indo-Australian Centre of Diversity.